Wavelength extension beyond 1.5 µm in symmetric InAs quantum dots grown on InP(111)A using droplet epitaxy. (27th September 2016) - Ha, Neul; Mano, Takaaki; Wu, Yu-Nien; Ou, Ya-Wen; Cheng, Shun-Jen; Sakuma, Yoshiki; Sakoda, Kazuaki; Kuroda, Takashi
Abstract: By using a C 3 v symmetric (111) surface as a growth substrate, we can achieve high structural symmetry in self-assembled quantum dots, which are suitable for use as quantum-entangled-photon emitters. Here, we report on the wavelength controllability of InAs dots on InP(111)A, which we realized by tuning the ternary alloy composition of In(Al, Ga)As barriers that were lattice-matched to InP. We changed the peak emission wavelength systematically from 1.3 to 1.7 µm by barrier band gap tuning. The observed spectral shift agreed with the result of numerical simulations that assumed a measured shape distribution independent of the barrier choice.